Designing and Manufacturing of Meat Grinding and Meatball Dough Blending Machine - Romiyadi; Indah Purnama Putri (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2017)
The purpose of the study was to design and manufacture of meat grinding and meatball dough blending machine with a capacity of 6 kg. In this study, researchers add more functions on meat grinding to meatball dough blending machine. From the process of designing and manufacturing, has produced a meat grinding and meatball dough blending machine with a capacity of 6 kg for a process. The machine uses a electric motor with a power of 0.25 HP. Based on the test results, meat grinding and meatball dough blending machine was able to meat grinding and meat ball dough blending and has efficiency of 96 % for the meat grinding process and 95 % for the meatball dough blending process.